ANALISIS SWOT PEDAGANG PASAR PALAKKA DALAM MENGHADAPI PERSAINGAN USAHA - Muh. Arafah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
The purpose of this research was to analyze the SWOT of Palakka market tradersand the working strategies implemented in facing the business competition. Basedon the results of the SWOT analysis, Palakka market traders were exercising themarket at affordable prices, various products, good services, and good orders.Meanwhile, the poor results came from old-fashioned products, limited capital,and less online advertisements. However, the opportunities came from fellowtraders as business partners, newly segmented or newly-targeted consumers,fluctuating market prices, and a religious-based attitude since they believe Godalready determined the sustenances. Unfortunately, some challenges were faced by Palakka market traders as a large number of users were dwindling outside themarket, poor road access, a large enough market area, and the latest productmodels. Palakka market traders may apply suggested strategies in facing businesscompetition based on the SWOT matrix analysis, starting with the SO strategy,including providing promotional prices or discounts to consumers and expandingmarket segmentation. Concerning that, another alternative, the WO strategy,included exchanging information among traders regarding the latest products andincreasing promotions both offline and online. Furthermore, the ST strategyincluded building familiarity with consumers and increasing the activeness ofmarket managers. The final strategy of WT includes increasing the quality andquantity of goods and increasing government participation.